Communication skills of medical doctors in Nigeria (2020)
Previous studies have reported communication problems between doctors and patients in clinical practice, and several barriers to effective doctor-patient communication. This study, therefore, was designed to determine the quality (good, fair or poor) and types of doctors’ communication skills, and challenges to doctor-patient communication in the country. The survey design was adopted and a multi-stage sampling procedure was used to select a sample size of 668 medical doctors. Quantitative data were analyzed using descriptive statistics, while the qualitative data were content-analyzed. Results showed that, among others, “active listening” was the predominant skill exhibited by medical doctors. The quality of the doctors’ communication skills was found to be “good.” However, the greatest challenge to doctor-patient communication was “patient deficiencies in literacy, language proficiency and education.”It is recommended that despite the challenges doctors should strive to maintain good communication by respecting patients’ rights and autonomy and promote patient understanding.